Comparative Analysis of Compressive Strength of Steel Tubing Pipe Welding Results Using SMAW and MIG Welding with 140A Current - Prasetia, Tengku Geby; Ariyon, Muhammad; Fitriani, Fitriani; Sebayang, Alexander; Tarigan, Efrata (International Journal of Engineering, Science and Information Technology, 2025)
The welding process plays a crucial role in manufacturing and is inseparable from its advancement. Deutsche Industrie Norman (DIN) defines welding as creating a metallurgical bond at the joint of metal or alloy metals in their molten state. This process is essential for constructing strong, durable materials like plates, steel, and pipes. Bending tests, including face bend and root bend, are often conducted to evaluate the quality of welded joints. These tests assess welded materials’ toughness, strength, and resistance under specific loading conditions. This study employed two welding techniques: Gas Metal Arc Welding (GMAW) and Shielded Metal Arc Welding (SMAW). GMAW, called Metal Inert Gas (MIG) welding, uses argon or helium as protective gases and a continuously fed electrode wire. On the other hand, SMAW relies on flux-coated electrodes to create the weld seam, with molten metal from both the electrode and parent material filling the joint. The results revealed distinct advantages for each method. The highest bending test value for the root bend was achieved with MIG welding at 982,55 Kgf/mm², demonstrating its effectiveness in creating durable root joints. Conversely, SMAW exhibited superior performance in face bend tests, achieving a bending strength of 104111 Kgf/mm², making it ideal for surface-level joint applications. Both techniques displayed no visible cracks in their welds, ensuring compliance with industry standards and confirming their reliability for various manufacturing needs. These findings highlight the importance of selecting appropriate welding methods based on specific application requirements.